Impact of electrical stimulation on the growth of mycelium of lignosus rhinocerus (cooke) ryvarden - Jamil N.A.M.; Gomes C.; Kadir Z.; Gomes A. (Taylor and Francis Ltd., 2023)
Dairies; Electric corona; Electric potential; Needles; Corona discharges; Direct-current injection; Electrical potential; Electrical stimulations; Growing environments; Growth enhancement; Multiple needles; Van de graff generators; Fungi; electrostimulation; growth, development and aging; mycelium; needle; Polyporaceae; Electric Stimulation; Mycelium; Needles; Polyporaceae